Coenzyme Q10 eyedrops conjugated with vitamin E TPGS alleviate neurodegeneration and mitochondrial dysfunction in the diabetic mouse retina - Lam, Christie Hang-I; Zuo, Bing; Chan, Henry Ho-Lung; Leung, Tsz-Wing; Abokyi, Samuel; Catral, Kirk Patrick Carreon; Tse, Dennis Yan-Yin (Frontiers in Cellular Neuroscience, 2024)
Diabetic retinopathy (DR) is a leading cause of blindness and vision impairment worldwide and represents one of the most common complications among diabetic patients. Current treatment modalities for DR, including laser photocoagulation, intravitreal injection of corticosteroid, and anti-vascular endothelial growth factor (VEGF) agents, target primarily vascular lesions. However, these approaches are invasive and have several limitations, such as potential loss of visual function, retinal scars and cataract formation, and increased risk of ocular hypertension, vitreous hemorrhage, retinal detachment, and intraocular inflammation. Recent studies have suggested mitochondrial dysfunction as a pivotal factor leading to both the vascular and neural damage in DR. Given that Coenzyme Q10 (CoQ10) is a proven mitochondrial stabilizer with antioxidative properties, this study investigated the effect of CoQ10 eyedrops (in conjunction with vitamin E d-α-tocopheryl poly(ethylene glycol) 1000 succinate (TPGS)) on DR-induced neurodegeneration using a type 2 diabetes mouse model (C57BLKsJ-db/db mice). Utilizing a comprehensive electroretinography protocol, supported by immunohistochemistry, our results revealed that topical application of CoQ10 eyedrops conjugated with vitamin E TPGS produced a neuroprotective effect against diabetic-induced neurodegeneration by preserving the function and histology of various retinal neural cell types. Compared to the control group, mice treated with CoQ10 exhibited thicker outer and inner nuclear layers, higher densities of photoreceptor, cone cell, and rod-bipolar cell dendritic boutons, and reduced glial reactivity and microglial cell density. Additionally, the CoQ10 treatment significantly alleviated retinal levels of MMP-9 and enhanced mitochondrial function. These findings provide further insight into the role of mitochondrial dysfunction in the development of DR and suggest CoQ10 eyedrops, conjugated with vitamin E TPGS, as a potential complementary therapy for DR-related neuropathy.